Ibn-al-Bauwāb -- ʿabqarī al-ḫaṭṭ al-ʿarabī ʿabra 'l-ʿuṣūr maǧmūʿa nafīsa min ḫuṭūṭ Ibn-al-Bauwāb - Ibn-al-Bauwāb, ʿAlī Ibn-Hilāl -1022; Nāǧī, Hilāl 1929- (Dār al-Ġarb al-Islāmī, 1998)
On Ibn al-Bawwāb, Arabic and Islamic calligrapher
Includes bibliographical references (p. 56-61) and indexes
Keywords: Ibn al-Bawwāb, ʻAlī ibn Hilāl / d. 1022; Ibn-al-Bauwāb, ʿAlī Ibn-Hilāl -- -1022; Calligraphy, Arabic; Arabic alphabet; Calligraphers / Arab countries; Arabische Schrift; Islam; Kalligrafie